PSIKOEDUKASI CARA MENJAGA KESEHATAN MENTAL DI TEMPAT KERJA BAGI KARYAWAN DI PERUSAHAAN X - Hairunnisa Putri; Elda Hasya; Ghaitsa Raodatul; M Ahkam Alwi (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Piling up work causes employees to experience stress and if prolonged will result in burnout which has an impact on mental health. Companies are usually unaware of the amount of work given to employees which causes the burden of employees to accumulate which can make them easily tired physically and stressed from the mind. Psychoeducation is one of the treatment strategies that can be applied in individual, family, and group settings that focus on psychoeducating participants about various problems faced in life, helping others to be better able to develop various sources of support from their environment, and developing coping skills to manage various problems. The method used in this activity is psychoeducation in the form of posters. The activity was carried out at PT X which began on 12 October, by conducting a literature study and conducting interviews with several employees at PT X to find out the conditions in the workplace or phenomena that are happening at PT X. The results obtained were that it had a positive impact on employees at PT X and could change employee behavior to maintain mental health in the workplace. Employees gave a positive response to the psychoeducation provided by doing some of the tips described in the posters that had been posted in the workspace.